PENGARUH SISTEM INFORMASI MANAJEMEN TERHADAP KINERJA KARYAWAN PADA PT.THAMRIN BROTHERS CABANG BATURAJA 1 - Amelia Agustina; Deo Melan Dwi Putra; Intan Sari; Hairin Nevia Putri; Hafiz Liyan Pratama; Novo Kurniawan (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2025)
This study aims to examine the effect of the Management Information System (MIS) on employee performance at PT Thamrin Brothers Baturaja 1. A quantitative research approach was employed, with the population consisting of all 33 employees of PT Thamrin Brothers Baturaja 1. Simple linear regression analysis was used as the analytical technique. The findings indicate that, partially, the Management Information System has a statistically significant effect on employee performance at PT Thamrin Brothers Baturaja 1. The results further reveal that the Management Information System accounts for 64.6% of the variation in employee performance, while the remaining 35.4% is explained by other factors not included in this study, such as motivation, compensation, work environment, workload, and other related variables.